"They say / I say" the moves that matter in academic writing - Graff, Gerald; Birkenstein, Cathy (W.W. Norton & Company, 2021)
"This book demystifies academic writing and shows how to engage with the views of others. Extensively revised in response to feedback from our community of adopters, this edition of They Say / I Say is an even more practical companion for students, featuring a new chapter on Researching Conversations, new exercises, expanded support for reading, and an expanded chapter on Revising. By focusing on the rhetorical moves found in all disciplines, They Say helps students master the ins and outs of argumentative writing in accessible language and with examples students can apply throughout their college career"--